Experimental Study on the Effect of Heating Duration on Compressive Strength of Fly Ash-Based Geopolymer Concrete from Bengkayang Power Plant - Mahazir, Muhamad; Herwani, Herwani; Faisal, Faisal (Jurnal Teknik Sipil, 2025)
Geopolymer concrete is an innovative construction material developed as an alternative to Portland cement. First introduced by Davidovits in 1978, geopolymer exhibits a chemical composition similar to zeolite but with an amorphous microstructure. One of its most significant advantages is its ability to reduce carbon dioxide emissions by approximately 80% compared to conventional concrete, making it a promising solution for mitigating the environmental impact of the cement industry. This study explores the utilization of coal-fired power plant waste to develop geopolymer concrete with varying heating durations, aiming to create a more environmentally friendly alternative that reduces pollution and lowers COâ‚‚ emissions from cement production. The experimental process involved producing test specimens using fly ash, NaOH, Naâ‚‚SiOâ‚ƒ, fine aggregates, and coarse aggregates, followed by mechanical property evaluations, including compressive strength, splitting tensile strength, and elastic modulus tests. The results demonstrated an average density ranging from 2,238.780 kg/m ³ to 2,323.662 kg/m ³, an average 28-day compressive strength between 15.279 MPa and 16.977 MPa, an average splitting tensile strength ranging from 1.320 MPa to 1.627 MPa, and an average elastic modulus (Chord Modulus method) between 2,838.251 MPa and 3,631.342 MPa. The optimal heating duration was identified as 24 hours, producing the highest 28-day compressive strength of 16.977 MPa. These findings confirm that fly ash is a viable substitute for cement in construction applications, offering a sustainable and eco-friendly alternative to traditional concrete.